The effect of staff development and policies on the performance of immigration personnel in northern Nigerian borders - Musalli, Naziru Mohammed (2016)
Border management has become a central issue in the contemporary global arena. Globalization has led to increasing flows of people, goods and services across regional borders. The porosity of borders in Nigeria which is loosely patrolled, resulted in massive influx of illegal immigrant and many other form of organized border criminal activities especially in north-eastern regions. Several initiatives on coordinated border management had been made both at regional and continental level with the purpose to address the issues related to border management. Yet there are growing number of concerns on how border will be managed effectively. Border management means the administration of borders, concerns with rules, procedures, processes, and techniques regulating the activities and traffic across defined border zones. The main objective of this study is to investigate the challenges and find out lasting solutions to the problems militating against the performance of border management personnel in Nigeria immigration service. The study unit of analysis is zone C of north-eastern Nigerian borders. Mixed-method of data collection was employed in this research of both quantitative and qualitative techniques, as a better means of problems solving than either method, where by number of questionnaires was distributed in the field. On the qualitative aspect an in-depth interview of face to face was employed to the study target population. The study empirically tested 4 hypotheses from the quantitative point of view in which 3 are supported and only 1 is not supported. The result indicated that there is significance relationship between organizational policies, infrastructural facilities and staff welfare to staff performance, while staff development has no significant effect to staff performance. Furthermore, result from the qualitative findings reveal that shortage of manpower, lack of training and re-training programme, inadequate provision of infrastructural facilities and lack of recruitment process based on merit and competency as well as porosity of borders impinge the realization of performance of personnel. The study concludes that government should put effective institutional framework that will immensely help in improving performance of Nigeria Immigration Service which would serve as panacea to border management crises bordering north-eastern Nigeria and the country at large.